The sports technology annual review and industry power list - Hopkins, R.; Thomas, D.; Carpenter, T.; Platt, J.; Martin, T. (2020)
The sports technology sector remains vibrant, diverse and continues to evolve. The sports technology world is, by its nature, subject to rapidly changing trends and movements. While eight years ago, the wearables market seemed unstoppable, it plateaued, rationalized, and now appears to be resurgent. Of the areas that have seen steady and continued growth, the one at the fore is data analysis, where various forms of Artificial Intelligence (AI) are being deployed to unearth new insights in both performance and fan engagement. Of course there are always technologies emerging in the commercial sector, and the challenge for any performance team can be where to direct attention, and what to ignore.